Research on Highly Pathogenic H5N1 Influenza Virus: The Way Forward - Anthony S. Fauci (American Society for Microbiology, 2012)
ABSTRACT The voluntary moratorium on gain-of-function research related to the transmissibility of highly pathogenic H5N1 influenza virus should continue, pending the resolution of critical policy questions concerning the rationale for performing such experiments and how best to report their results. The potential benefits and risks of these experiments must be discussed and understood by multiple stakeholders, including the general public, and all decisions regarding such research must be made in a transparent manner.